Prevalence and Anatomical Distribution of Accessory and Replaced Hepatic Arteries: Implications for Hepatobiliary Surgery in Peshawar - Shehla Khatoon, Zainab Rehman, Parkha Rehman, Sarah Rehman, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Anatomical variations of the hepatic arterial system are frequently encountered during hepatobiliary surgery and may significantly influence operative safety. Accessory and replaced hepatic arteries, if unrecognized, can predispose patients to vascular injury, hepatic ischemia, biliary complications, and postoperative hemorrhage. Population-specific data regarding these variations remain limited in Khyber Pakhtunkhwa. Objective: To determine the prevalence and anatomical distribution of accessory and replaced hepatic arteries in patients undergoing hepatobiliary surgery in Peshawar and to assess their surgical implications. Methodology: A prospective observational study was conducted at the Surgical “B” Unit of Khyber Teaching Hospital, Peshawar, over one year, from January 2020 to January 2021. A total of 139 patients undergoing open hepatobiliary surgical procedures were enrolled. Intraoperative identification of accessory and replaced hepatic arteries was performed, and their anatomical characteristics were documented using a structured proforma. Data were analyzed descriptively using SPSS version 25. Results: Accessory and replaced hepatic arteries were identified in 60 patients (42.8%). Replaced right gastric artery was the most frequent variant (22.0%), followed by accessory right hepatic artery (6.5%) and accessory cystic artery (5.75%). Multiple aberrant arteries were present in 18 patients (12.9%). The distribution of arterial variants was statistically significant (p < 0.001). Conclusion: Accessory and replaced hepatic arteries are common and clinically significant anatomical variations in hepatobiliary surgery. Awareness and careful identification of these vessels are essential to minimize intraoperative complications and to optimize surgical outcomes.